Enhancing the Ability of the Square Footing to Resist Positive and Negative Eccentric-inclined Loading Using an Inclined Skirt (Journal of Engineering, 2024)
Shallow and inclined skirted foundations on 30% sandy soil were examined in the experiment program. The study examined the effects of positive and negative eccentric-inclined loading on foundations. Experimental testing was done in a 600 × 600 mm box with a 50 x 50 mm square footing with a 10 mm thickness. The skirt angles were 10°, 20°, and 30°, and the skirt depth was Ds was 0.5 B. Results showed that using skirts significantly increases load-bearing capacity and decreases tilting. Tilting reduces with a skirt, and skirt inclination (alpha) increases with similar loads. Inclined skirts decrease tilt by (2.3% to 0.66%) at e was 0.15 B, load angle (beta) was 15°, and alpha was 30° in the negative case. Tilting increases with eccentricity. As load inclination grows, unskirted and skirted foundations slide and rotate. For the positive case, the tilting decreases from 10% to 2% with e was 0.15 B, loading angle (beta) was 15°, and alpha was 30° with an inclination skirt. The amount of horizontal displacement of the skirted foundation is more than that of the unskirted foundation when comparing the failure load for the unskirted foundation with the same load for the skirted foundation. Loading a foundation without a skirt causes significant settlement and little horizontal displacement. Increasing the load angle is effective since it greatly affects horizontal displacement. In some situations, such as a negative eccentric-inclined load with Ds was 0.5 B, beta was 15, and e was 0.05 B, the influence of the loading angle may be decreased once failures with eccentricity. When eccentricity increases while the load angle (beta) remains constant, the horizontal displacement of a negative eccentric-inclined load reduces.